Work-Life Balance pada Karyawan Wanita dan Implikasinya terhadap Kinerja dan Kesejahteraan - Enjelia Hulu; Renny Aprilliyani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse work-life balance among female employees and its impact on performance and well-being in manufacturing companies. The problem focuses on how female employees manage the balance between work demands and family responsibilities. The study applies work-life balance, employee performance, and well-being concepts as theoretical foundations. Data were collected through in-depth interviews with eight female employees, supported by observation and documentation, and analysed qualitatively. The findings show that work-life balance is influenced by job demands, family responsibilities, organisational support, and individual strategies. A balanced condition improves work focus, productivity, and psychological well-being, while an imbalance leads to emotional exhaustion. This study concludes that organisational support and individual capability in managing dual roles are key factors in achieving sustainable work-life balance and enhancing employee performance and well-being.